PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 102 PEKANBARU - Anisma Anisma; Munjiatun Munjiatun; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This observation was conducted by the IPA learning results which not achieve School KKM target score set by 65. On this case, observations are required to enhance learning process and raise student achievements for IPS Subject. The observation s is conducted to Class III SD Negeri 102 Pekanbaru Period 2014/2015 by applied Cooperative teaching methods Type Think Pairs Share (TPS) where first cycle conducted on April to Juni 2015. The observed student on Class III SD Negeri 102 Pekanbaru are 24 students, the Observation was observe Teacher’s activities, student’s activities and learning result orstudents achievement. Look up to observed students learning result, will show the average score achieved by students is increased. On average basis score 62,29 with classical completion 41,66% (incomplete) . increased on first cycle Average score is 70,20 with classical completion 62,5%(incomplete) and second cycle 84,16 with classical completion 91,66%(complete). The observation shown the relations of teacher and students activities to learning result , teacher activities on first cycle first meeting is 77,5% within good category. Second meeting is 87,5% within good category, by the second cycle first meeting is 82,5% within good category, and second meeting is 95% within very good category. The observation conclude that applying Cooperative type learning method type Think Pair Share(TPS) is able to enhance / increase learning achievement on Students Class IIISD Negeri 102 Pekanbaru.Keyword :Think Pair Share (TPS), Sains result